RISIKO LIKUIDITAS SEBAGAI PENGINDIKASI SYSTEMICALLY IMPORTANT BANKS: INDONESIA 2007 - 2014 - Karin Diandra (Bina Ekonomi, 2017)
Funding liquidity issues have become the main cause of crisis particularly due to banks’ interconnectedness. This study assesses funding liquidity risk faced by Indonesian banks and also identified which bank can be classified to systemically important banks (SIBs). Each bank’s funding liquidity risk is measured by the distance between the real liquidity condition and the ideal condition, while the identification of SIBs is based on the size and interconnectedness of every bank. This study employs liquidity mismatch index which contains of relative liquidity surplus and absolute liquidity surplus to current assets and current liabilities of 80 Indonesian conventional banks from January 2007 until December 2014. The result according to the relative liquidity surplus is that Indonesian banking system’s liquidity condition is near to the ideal condition, yet there are few banks experiencing too much excess liquidity. According to the absolute liquidity surplus, the result is that banks with higher core equity (classified in BUKU 3 and 4) are more potentially to become SIBs. Keywords: funding liquidity risk, systemically important banks, relative liquidity surplus, absolute liquidity surplus, risk contribution